Study speaking: a course in spoken english for academic purposes - Anderson, Kenneth; Maclean, Joan; Lynch, Tony (Cambridge : University Press, 2004)
Language and Literature
Keywords: Spoken english; Presentation skills; Class seminars; Teacher's guide; Discussion skills; Class seminars; Education